Emotion regulation and subjective wellbeing among Turkish population: the mediating role of COVID-19 fear - Can, Gürhan; Candemir, Gülşah; Satıcı, Seydi Ahmet (Springer, 2022)
We examined fear of COVID-19 as a mediator of the relationship between emotion regulation (suppression, reappraisal) and subjective wellbeing. In this cross-sectional study, 1,014 Turkish individuals completed assessments of positive affect, negative affect, satisfaction with life, emotion regulation (suppression, reappraisal), and fear of COVID-19. Network analysis revealed that all variables were associated with each other. Structural equation modelling indicated that greater suppression was associated with greater fear of COVID-19 and less subjective wellbeing. Greater reappraisal was associated with less fear of COVID-19 and greater subjective wellbeing. In addition greater suppression was associated with less subjective well-being and greater reappraisal was associated with greater subjective well-being. Mediation analyses demonstrated that fear of COVID-19 partially mediated the relationship between suppression, reappraisal and subjective wellbeing. Findings expand our understanding of the link between emotion regulation and subjective wellbeing during the COVID-19 pandemic. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: COVID-19 fear; emotion regulation; subjective wellbeing